Closure beyond clozapine: successfully averting rebound symptoms in a patient with schizoaffective disorder and agranulocytosis - Alastair Green; Thomas Stephenson; Eromona Whiskey; Sukhi S. Shergill (BJPsych Open, 2019)
Summary‘Rebound’ or ‘withdrawal’ symptoms are frequently observed after a sudden discontinuation of clozapine. We describe a patient with treatment-resistant schizoaffective disorder who developed agranulocytosis on clozapine but was successfully switched to treatment with olanzapine with no deterioration in her condition. We put forward three possible theories which may have accounted for the lack of rebound symptoms in this patient: the pharmacological profile of olanzapine, the anticholinergic effects of hyoscine hydrobromide, and the possibility that this patient may not be treatment-resistant and so have a reduced risk of rebound psychosis due to displaying a different pathophysiology.Declaration of interestNone.